Henry VIII : wolfman - Moorat, A. E. (New York : Pegasus Books, 2011)
Five hundred years ago Henry VIII had a fearsome temper and bloodthirsty reputation to match; more beast than human, some might say ... Is it possible he was really a werewolf?!? Discover the man behind the myth - and behind the fur - in this inventive retelling of Henry's reign
Originally published: London: Hodder & Stoughton.
Keywords: Demonology -- Fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Black humor